EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN “GAUL GASI” (GAME EDUKASI ULAR TANGGA AKUNTANSI) UNTUK MENINGKATKAN ANTUSIASME BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the lack of enthusiasm of students in learning accounting. The purpose of this study was to analyze the effectiveness of using learning media GAUL GASI (Educational Game, Snake and Ladder Accounting) in increasing student enthusiasm for learning in accounting subjects. This research is a quasi experimental design with one group pre test-post test. The research was conducted at SMK 3 Muhammadiyah Pekanbaru in Class X Accounting. Data obtained through questionnaires and analyzed through data normality test and paired sample T test. The results showed that the mean value of theresults pre-test was 29.75; while for theaverage score was post-test found to be 33.52; and thevalue tof -5.011 with sig (2 tailed) 0,000. This shows that there is a difference between the pre-test and thescores of post-test the students' enthusiasm for learning. Because the t value is found to be negative, it means that the post-test score is better than the pre-test score. The occurrence of differences and changes in the level of student enthusiasm for learning becomes very good, so that the learning media GAUL GASI (Accounting and Snake Ladder Educational Game) is effectively used to increase student enthusiasm for learning.Key Words: Enthusiasm, Learning Media, Educational Game, Snake and Ladder Accounting (GAUL GASI)